2021
DOI: 10.1021/acs.jafc.1c05617
|View full text |Cite
|
Sign up to set email alerts
|

Nanoselenium Enhanced Wheat Resistance to Aphids by Regulating Biosynthesis of DIMBOA and Volatile Components

Abstract: Aphids are one of the most destructive insects in many cultivated plants including wheat, which can cause significant yield loss and damage the quality of agricultural products. Therefore, it is essential to control the occurrence of aphids during wheat growth. Previous studies reported the alterations in the resistance of wheat to pests induced by several external factors such as nutrients in soils and nano-carbonaceous materials. In this study, nanoselenium (nano-Se) was sprayed on wheat leaves at several co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Minor adjustments were made to the DIMBOA (2,4-dihydroxy-7methoxy-1,4-benzoxazin-3-one) detection technique utilized in a prior work. 26 This involved extracting 100 mg of ground wheat leaves, roots, and rhizosphere soil samples with 1 mL of methanol (containing 1% formic acid) at 4 °C for 24 h. The samples were then homogenized for 5 min using ultrasounds before centrifugation for 5 min at 12 000 rpm. After collecting the resulting supernatants, the above-mentioned process was repeated three times.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor adjustments were made to the DIMBOA (2,4-dihydroxy-7methoxy-1,4-benzoxazin-3-one) detection technique utilized in a prior work. 26 This involved extracting 100 mg of ground wheat leaves, roots, and rhizosphere soil samples with 1 mL of methanol (containing 1% formic acid) at 4 °C for 24 h. The samples were then homogenized for 5 min using ultrasounds before centrifugation for 5 min at 12 000 rpm. After collecting the resulting supernatants, the above-mentioned process was repeated three times.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A modified method of the MT approach was employed in a prior study. 26 Liquid nitrogen was used to grind wheat tissues (leaves, roots, and rhizosphere soil), with 100 mg of wheat tissues subsequently extracted with 1 mL of extracting solution (acetonitrile/hexane = 80:20, V/V). After applying ultrasounds for 30 min, the resultant homogenate was centrifuged for 5 min at 12 000 rpm.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Whether SA promotes or inhibits plant growth depends on the species of plant and concentrations of expressed SA. 42 JA is also a key factor in the regulation of the defense responses inhibiting invasion by herbivores or saprophytic pathogens. 43 Similar to SA, the production of JA also affects plant development and is a plant senescence promoter and root growth inhibitor.…”
Section: Growth and Defensementioning
confidence: 99%
“… Moreover, the production of SA not only affects the resistance of plants to pathogens and herbivores but can also influence the morphology of leaves as well as root and flower development. Whether SA promotes or inhibits plant growth depends on the species of plant and concentrations of expressed SA …”
Section: Trade-off Between Growth and Defensementioning
confidence: 99%
“…Studies showed that nano-Se may be utilized as biofortifiers and stimulators, and its effect on plant antioxidant metabolism was related to primary and secondary metabolites ( 20 ). Our previous studies demonstrated that foliar application of nano-Se regulated hormone pathway, phenylpropane pathway, volatile organic compounds, antioxidants enzymes, and secondary metabolites to strengthen the quality and resistance in various crops ( 21 23 ). Medical studies revealed that the protective mechanism of Se on the human body includes inhibition of oxidative stress, endothelial dysfunction, protection of vascular cells from apoptosis, calcification, and regulation of inflammation ( 24 ).…”
Section: Introductionmentioning
confidence: 99%